Modification of Polycrystalline PV String for Charging on Electric Scooter - Hazrina, Fadhillah; Purwiyanto, Purwiyanto; Ali, Naufal; Widiyanto, Syam (MSD Institute, 2024)
Electric scooters rely on batteries to power BLDC motors, which are traditionally recharged through the household electricity grid. However, alternatives like solar energy are being explored to reduce dependency on conventional power sources. A challenge arises due to the discrepancy in voltage compatibility between standard solar panels and scooter batteries. Typically, a 36 V scooter battery requires a higher voltage input than the 18 V output of a single solar panel. This requires modifications to align solar cell design with battery voltage requirements. This study implements a PZEM-015 sensor for monitoring battery energy consumption. The contribution of this study is twofold: to develop and optimise solar cell modification for effective battery charging and to assess battery consumption concerning speed and travel duration. Testing reveals that a series circuit modification yields an average voltage of 39.2 V and an average current of 0.55 A, resulting in 21.8 Wp of power output. Analysis of scooter performance indicates that maintaining speeds between 4.16 m/s and 5.55 m/s significantly extends travel time and conserves battery energy. These findings highlight the potential of modified solar PV in enhancing electric scooter efficiency and sustainability.